REGULASI EMOSI UNTUK PENINGKATAN PERILAKU PROSOSIAL PADA REMAJA DI WAHANA VISI INDONESIA KOTA SURABAYA - Monica Elisabeth; Stephanie Tarradea; Hartanti Hartanti (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Transitioning into adolescence, teenagers have the tendancy to be in “Storm and Stress” condition, where they will start to grow emotional turmoil and not be able to control their emotion. This condition might be one of the conflict triggers in Forum Anak Wahana Visi Indonesia club committee in Surabaya. The forum members became more sensitive of any dissents and it created some conflicts in the social environment, not only in the organization, but also in family and school. Thus, it is difficult for teenagers to be prosocial with others. This research used the qualitative and quantitative methods to identify the problem and for measuring the success of the training. The plan of the training was arranged based on the result of a survey that was given to 20 teenagers with 13-18 year old age range. The training was performed 2 days with 10 participants who managed to do all the training activities. According to the statistical analysis, the result showed that p > 0,05. It means that the questionnaire data collection showed no significant change related to the participants' ability in showing the prosocial behavior in daily life. This result was caused by the time range of the data collection, where the conflicts had not happened and there was no supportive situation that might trigger the prosocial behavior.